Tests of Inclined Concrete-Filled Steel Tubular Stub Columns under Vertical Cyclic Loading - Chayanon Hansapinyo; Chinnapat Buachart; Preeda Chaimahawan (Advances in Civil Engineering)
This paper presents an experimental study on the cyclic behavior of fifteen concrete-filled steel tubular columns subjected to vertical cyclic loading. All test samples’ cross-sectional area is 75 × 75 mm2 square, and they are 500 mm long. The main variables in the test are the thickness of the steel tube (1.8 and 3.0 mm with the width-to-thickness ratios (b/t) of 41.7 and 25), the strength of the infilled concrete (no-fill, 23 MPa, and 42 MPa), and the inclined angle (0, 4, and 9 degrees). The results show that all samples failed due to local buckling in compression followed by tearing of the steel tube in tension. The inclination angles of 4 and 9 degrees decreased the vertical compressive capacity of the 1.8 mm vertical hollowed steel column by 34 and 39 percent, respectively. However, the infilled concrete and thicker tube (3.0 mm) could substantially reduce the adverse effect of the inclination angle. The compressive ductility of the hollowed column with the thinner tube was significantly enhanced by the infilled concrete as well.